Rancang Bangun Aplikasi Bank Sampah Berbasis Android - raihan muhammad, alwi; supriyadi, dede (Liaison Journal of Engineering, 2023)
Population growth and changes in people& consumption patterns lead to an increase in the volume, types, and characteristics of increasingly diverse waste. However, waste management so far has not been in accordance with environmentally sound waste management methods and techniques, resulting in negative impacts on public health and the environment. Waste Bank emerged as a local community initiative in an effort to participate in dealing with existing problems. The community- based 3R (Reduce, Reuse, and Recycle) waste management strategy, is able to change the image of most people towards waste that has no economic value into economic value. The Muda Karya Garbage Bank in RW 01 Pondok Cabe Ilir Village in all processes of data collection and writing of customer transactions, as well as monthly reports still uses customer passbooks and monthly reports, so transaction data storage is not well organized. As for the design, the researcher uses an object- based method with UML (Unified Method Language) tools. The Information System for the Young Waste Bank of Karya Pondok Cabe Ilir can be accessed by admins and customers. Admin can manage waste deposit transactions and withdrawals of customer balances. Customers can change profile data, view garbage deposit history, and balance withdrawal history. An android-based information system for the Karya Muda Pondok Cabe Ilir Garbage Bank that is connected to the internet network allows users to access information every day in order to assist in obtaining information on the Pondok Cabe Ilir Young Garbage Bank and make it easier for admins to manage waste deposit transactions and customer balance withdrawals. Keywords: Information System, Muda Karya Waste Bank, Waste Bank, Java, UML, Waterfall.